2012
DOI: 10.1007/s00128-012-0795-4
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Metals in Tissues of Ctenopharyngodon idella and Perca fluviatilis, from Anzali Wetland, Iran

Abstract: The objective of the present study was to investigate the levels of metals (Cd, Cu, Zn, Pb and Cr) in muscle, gill, liver, kidney and intestine of two freshwater fish, Ctenopharyngodon idella and Perca fluviatilis, in Anzali Wetland, Iran. The concentrations were different between the fish species as well as among the tissues of fish. Results showed that the metal concentrations in both fish species were in descending order of Zn > Cu > Pb > Cr > Cd. Results also showed that the Cd, Cu, Zn, and Pb concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…Agreement can be seen with Tekin-Ozan and Kir (2008) and Norouzi et al (2012) findings who claimed muscles are not an active organ for binding metals in fish species. However, Baramaki et al (2012) findings confirms that the metal concentrations of Ctenopharyngodon idella and Perca fluviatilis, captured from Anzali wetland, were also higher in gill. Dsikowitzky et al (2013) surveyed several freshwater fish species from Awassa and Koka Rift Valley Lakes, Ethiopia, and reported that metal concentrations were generally higher in their gills compare to muscles.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…Agreement can be seen with Tekin-Ozan and Kir (2008) and Norouzi et al (2012) findings who claimed muscles are not an active organ for binding metals in fish species. However, Baramaki et al (2012) findings confirms that the metal concentrations of Ctenopharyngodon idella and Perca fluviatilis, captured from Anzali wetland, were also higher in gill. Dsikowitzky et al (2013) surveyed several freshwater fish species from Awassa and Koka Rift Valley Lakes, Ethiopia, and reported that metal concentrations were generally higher in their gills compare to muscles.…”
Section: Resultssupporting
confidence: 75%
“…According to Food and Agriculture Organization (FAO 1983) standards, the concentrations of Cd, Cu, Zn, and Pb in the muscle of C. carpio and H. molitrix from Zabol Chahnimeh reservoirs are below levels of concern for human use. Due to lack of information, the Cr ion is not usually an analytical target within routine surveillance of pollutants in fish (Storelli et al 2005;Baramaki et al 2012). The comparison of metal concentrations with other regions of the world, shows that Cd and Pb concentrations in the muscle of C. carpio and H. molitrix from the present study were higher than those in (1) Hypophthalmichthys molitrix, Chondrostoma nasus, and Alburnus alburnus from Zagreb, Croatia (Zrnčić et al 2013), (2) Hypophthalmichthys molitrix, Ctenopharyngodon idellus, and Megalobrama amblycephala from China (Zhuang et al, 2013), and (3) Labeo calbasu, Cirrhinus reba, and Rita rita from Chenab River, Pakistan (Waheed et al 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cadmium content was also higher in liver than muscles of both species (tench and perch) from the southwest of the Caspian Sea (Iran) (Eslami, Sattari, Namin, & Ashrafi, 2014). Yazdi, Ebrahinpour, Mansouri, Rezaei and Babaei (2012) reported that the content of cadmium was different between the tissues of perch (intestine > liver > gills > muscles). There were significant differences between the content of Cd in organs of pike (muscle, gill, kidney, intestine and liver) from Anzali Wetland (Iran), because the cadmium content in fish decreased in the following order: liver > kidney > gills > intestine > muscles (Ebrahimpour, Pourkhabbaz, Baramaki, Babaei, & Rezaei, 2011).…”
Section: Resultsmentioning
confidence: 99%